Inai Dance and Cultural Identity in Malay Wedding Ceremonies of Teluk Majelis - Nurul Annisa Syafwan; Daryusti Daryusti (Gondang: Jurnal Seni dan Budaya, 2025)
The Inai Dance is a traditional dance that is only performed in traditional wedding ceremonies in Teluk Majlis Village for the Malays. This Inai dance is performed during the evening Henai Dance procession, which is held on the night before the wedding day. The Inai dance has been performed by people from the past to the present, so it has become a characteristic in the village of Teluk Majlis. This research uses a qualitative approach, which was carried out in Teluk Majlis village. The informants in this study are traditional leaders, studio leaders, dancers, and community users who hold the Inai dance night ceremony in Teluk Majlis village. Data collection used observation, interview and documentation techniques. The source triangulation technique is a technique used to ensure the validity of this data. To analyze data requires steps such as data collection, data presentation, and drawing conclusions. The result of this study is that the Inai Dance plays an important role as a marker of the existence of the Malay community in the midst of the dynamics of modernization and intercultural interaction. Despite the mixture of ethnicities and social changes, the people of Teluk Majelis Village still strive to maintain this cultural practice as a form of fortitude in their identity and a symbol of cultural unity.